Pelatihan Komersialisasi Produk Bagi UMKM Keripik Di Gampong Karang Anyar Kota Langsa - Puti Andiny; Dewi Rosa Indah; Rahmi Meutia (Universitas Teuku Umar, 2021)
The role of the wholesale and retail trade sector, car reparation and motorcycle repair ranks first among other sectors and has a direct effect in accelerating economic activity to produce goods and services. The role of this sector during the 2015-2019 period fluctuated to reach the level of 30.60 percent in 2019. Gampong Karang Anyar has 3 Cassava chip industries that are still underdeveloped. It is due to the lack of innovation in products, traditional marketing strategy and low information technology marketing utilization. Based on these problems, business actors need deeper knowledge of business management concept for product commercialization, especially related to packaging design and marketing that utilize information technology. The method of implementing this community service activities was counseling or socialization for improving packaging and marketing designs as well as training and mentoring for digital marketing by using Google My Business platform. By having this activity, partners are expected to be better in managing their business and capable to expand market share so that they can support business development and progress, which can increase business income.